Islamic Banking Research in Indonesia: A Bibliometric Mapping Using Scopus and Biblioshiny - Mainata, Dedy; Pratiwi, Angrum (JESI (Jurnal Ekonomi Syariah Indonesia), 2025)
Introduction: Islamic banking in Indonesia is an expanding scholarly domain. This study maps the development of Islamic banking research by analyzing Scopus-indexed publications. Despite rising output, comprehensive bibliometric assessments of Indonesia’s Islamic banking literature remain limited; the study asks what thematic trends, author productivity, and future research directions characterize the field. Using biblioshiny, the paper delivers a consolidated, Scopus-based national mapping that visualizes how the domain has evolved within Indonesia’s academic context. Methodology: We analyze 201 Scopus-indexed documents with RStudio’s Biblioshiny, applying descriptive statistics, co-occurrence analysis, thematic evolution, and clustering to reveal patterns, author networks, keyword trends, and intellectual structures. Results: Publications show steady growth with a marked post-2015 surge. Core themes include Islamic finance, Sharia compliance, and Islamic fintech, alongside identifiable key authors, journals, and institutions. The field is shifting from conceptual discussions to empirical and application-oriented work, consistent with Price’s Law and Kuhn’s “normal science.”Conclusion: The study clarifies knowledge growth in Indonesia’s Islamic banking scholarship and offers guidance for future research agendas, policymaking, and industry engagement, emphasizing collaboration among academics, regulators, and practitioners to strengthen the ecosystem and support inclusive, sustainable financial development.